Promoting Educational Persistence in Crisis Regions: Insights From Students’ Experiences of Online Learning in the University of Buea - Mercy Aki Etta (Indonesia Approach Education, 2024)
Higher education in Cameroon continues to suffer from the effects of a twin crisis including a current socio-political armed conflict (in its two English-speaking regions) and the COVID-19 pandemic that has left school activities irregular in these regions. However, COVID-19 has brought about an automatic educational change requiring a transition to online learning that provides a window of opportunity for educational persistence in these crisis regions. Regardless of this, students’ voices of their experiences of online learning in the context of pandemics and armed conflicts are almost missing. This paper provides an assessment of students’ perceptions about their experiences with online learning in the wake of COVID-19 using Diffusion of Innovation theory as a framework to describe the (1) relative advantage (2) trialability and (3) complexity of online learning. The study adopted a survey design and data were collected from 1436 students randomly selected from the University of Buea, Cameroon. Findings from frequency counts, percentages, chi-square and thematic analyses revealed that students view online learning as an opportunity for educational persistence in crisis regions, however, trialability is low with younger and undergraduate students having limited online learning experiences (P<0.01). Similarly, students viewed online learning as complex, compounded by enormous challenges to which decision makers can address to sustain learning in armed conflict. To this end, it is recommended amongst others that course syllabuses should be re-organize to include at least 4 hours of online learning to improve students’ online learning experiences and promote educational persistence in crisis regions.